Business models in the industry 4.0 environment' results of web of science bibliometric analysis - Sandra Grabowska; Sebastian Saniuk (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The Fourth Industrial Revolution affects the operations of companies and results in new strategic thinking. The changes resulting from the requirements of Industry 4.0 force restructuring in many areas of management or the building of new business models. The aim of this article was to indicate the pillars that will form the basis for building business models of enterprises functioning in the era of Industry 4.0. The research methods used in this article were bibliometric analysis and analysis of the content of sophisticated publications. The results of this research are the analysis of the dynamics of publications in the area of business models in the era of Industry 4.0, an indication of the research areas undertaken in these publications and the identification of the pillars that will constitute the basis for building business models in the era of Industry 4.0. Business models in the era of Industry 4.0 are to be a method of increasing and using the company's resources in order to achieve a competitive advantage through personalization of products and their new quality; their key competitive advantage will be a structure based on a network of cyber-physical cooperation. This article is dedicated to scientists and business practitioners looking for tips for building modern business models.
Keywords: 650; business model; Fourth Industrial Revolution; Industry 4.0; open business model; open innovations; pillars of the business model